Comparison of different adjuvant analgesia for paravertebral block in video-assisted thoracoscopic surgery: A double-blind randomized controlled trial - Rong Tang; Wen-sheng Lu; Hai-lian Zhong; Fang Wu; Yu-Qian Liu (PLoS ONE, 2025)
Background Local anaesthetic adjuvants have been shown to provide better pain relief and extend the duration of analgesia. But little information is available on which adjuvants are more effective in block extension for thoracic paravertebral block (TPVB) during video-assisted thoracoscopic surgery (VATS). This study aimed to compare the analgesic efficacies of different adjuvants with 0.375% ropivacaine in ultrasound-guided TPVB for VATS. Methods A total of 120 patients who underwent VATS at the study hospital in 2022–2023 were recruited and randomly divided into four groups, including the control group (Group R), which received 20 ml ropivacaine 0.375% for TPVB, and the intervention groups: Group D (0.375% ropivacaine with 1 µg/kg dexmedetomidine in a total of 20 ml for TPVB), group E (0.375% ropivacaine with 0.1 mg/kg dexamethasone in a total of 20 ml for TPVB), and group S (0.375% ropivacaine with 0.5ug/ml sufentanil in a total of 20 ml for TPVB). They received a single-injection ultrasound-guided unilateral T5-level TPVB. The primary clinical outcomes were visual analogue scale (VAS) pain scores at rest and during coughing at 4, 8, 12, 16, 20, 24, and 48 h postoperatively. Secondary outcomes included opioid consumption, number of patient-controlled intravenous analgesics (PCIA) used within 48 h, postoperative rescue analgesia, side effects, quality of recovery after surgery, and length of hospital stay. Results We found that the VAS pain scores in the resting state during the postoperative period at 12–20 h were lower in Group D than in Group R (P < 0.05). The resting VAS pain scores of Groups E and S were lower than those of Group R during the postoperative period of 12–16 h (P < 0.05). Similar differences were observed in the pain scores during coughing at the same time points. Additionally, the co-administration of adjuvants with ropivacaine were associated with decreased consumption of postoperative opioids, less frequent PCIA use, and earlier time to ambulation. The intergroup pairwise comparisons showed that dexmedetomidine was more effective than dexamethasone and sufentanil in reducing additional postoperative analgesics, the length of chest tube placement and length of hospital stay. Subsequently, we administered questionnaires on the quality of recovery, which was positively correlated with the postoperative analgesic effect. Conclusions These findings suggest that adjuvant analgesia for TPVB can improve postoperative pain in patients undergoing VATS. However, compared with dexamethasone and sufentanil, dexmedetomidine is more effective in extending the duration of analgesia, reducing the demand of postoperative analgesics, improving the quality of recovery at 48 h postoperatively and shorting the length of hospital stay.